2010
DOI: 10.1021/jp910245k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study on Glass Transitions in Atactic-Polypropylene Bulk and Freestanding Thin Films

Abstract: Molecular dynamics simulation has been adopted in investigation of different glass transition behaviors of the bulk and the freestanding thin films (about 8 nm) of atactic polypropylene (a-PP). For characterization of glass transition temperature (T(g)) of above systems, both the specific volume and the local conformational transition rate of the systems were examined. The T(g) characterization from the local conformational transition rate of polymer chains was recently developed. Our simulation results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 61 publications
6
29
1
Order By: Relevance
“…In view of gratifying success of MD in many research fields and a high degree of similarity of the temperature dependence of the specific volume between experimental observations and simulation calculations, it has reason to believe that we can get insight into microscopic details about the microstructure and molecular motion by MD. In order to illustrate the justifiability of our simulation calculations, Figure gives the running average of specific volume obtained during dynamics simulations against simulation time at the several specified temperatures for a‐PP of this work, which are reasonable consistent with the reports in literature . Figure is the corresponding relationship between the average specific volume and temperature in the equilibrium state, when the fluctuation of the average values is negligible small.…”
Section: Resultssupporting
confidence: 80%
“…In view of gratifying success of MD in many research fields and a high degree of similarity of the temperature dependence of the specific volume between experimental observations and simulation calculations, it has reason to believe that we can get insight into microscopic details about the microstructure and molecular motion by MD. In order to illustrate the justifiability of our simulation calculations, Figure gives the running average of specific volume obtained during dynamics simulations against simulation time at the several specified temperatures for a‐PP of this work, which are reasonable consistent with the reports in literature . Figure is the corresponding relationship between the average specific volume and temperature in the equilibrium state, when the fluctuation of the average values is negligible small.…”
Section: Resultssupporting
confidence: 80%
“…According to the free volume theory, the density or its reciprocal, specific volume of system will vary greatly when the system cools down from high to low temperature across the glass transition temperature, which is determined by finding the point of intersection of the fitted lines in the rubbery and glassy regions. This method has been adopted in many simulation researches . First, we focus on the influence of the cooling rate on the T g for the chain structure I, which is shown in Figure (a).…”
Section: Resultscontrasting
confidence: 63%
“…The change of T g seriously depends on the interfacial interaction and the mobility of the confined boundary . Furthermore, the freestanding thin films of atactic polypropylene have lower T g than the bulk, and the descent of T g is in a range of 10–30 K . This is due to the increase of free volume near the surface region of thin films .…”
Section: Introductionmentioning
confidence: 94%
“…42 By using the single-molecule uorescence microscopy, Wöll's group found that the temperature dependence of fraction of mobile molecules in polystyrene lms exhibited similar trends with that of PSM. [26][27][28][29][30][31][32] Similarly, we also observe the conformational changes during cooling in the current simulation. [26][27][28][29][30][31][32] Similarly, we also observe the conformational changes during cooling in the current simulation.…”
Section: Resultsmentioning
confidence: 56%
“…13,14 For instance, the structural characteristics of CRR are still unknown. [27][28][29][30][31][32] The increase of the fraction of transconformations may induce the formation of the short-range order in polymers. For colloidal system, Tanaka et al 23,24 and Yodh et al 25 detected the formation of some local ordered structures during cooling, and they argued that the development of the local ordered structures may be the origin of the slow dynamics.…”
Section: Introductionmentioning
confidence: 99%